Morphological and Immunohistochemical Characterization of Canine Osteosarcoma Spheroid Cell Cultures. (19th August 2015) - Gebhard, C.; Gabriel, C.; Walter, I.
Summary: Spheroid cell culture emerges as powerful in vitro tool for experimental tumour research. In this study, we established a scaffold‐free three‐dimensional spheroid system built from canine osteosarcoma (OS) cells (D17). Spheroids (7, 14 and 19 days of cultivation) and monolayer cultures (2 and 7 days of cultivation) were evaluated and compared on light and electron microscopy. Monolayer and spheroid cultures were tested for vimentin, cytokeratin, alkaline phosphatase, osteocalcin and collagen I by means of immunohistochemistry. The spheroid cell culture exhibited a distinct network of collagen I in particular after 19‐day cultivation, whereas in monolayer cultures, collagen I was arranged as a lamellar basal structure. Necrotic centres of large spheroids, as observed in 14‐ and 19‐day cultures, were characterized by significant amounts of osteocalcin. Proliferative activity as determined by Ki‐67 immunoreactivity showed an even distribution in two‐dimensional cultures. In spheroids, proliferation was predominating in the peripheral areas. Metastasis‐associated markers ezrin and S100A4 were shown to be continuously expressed in monolayer and spheroid cultures. We conclude that the scaffold‐free spheroid system from canine OS cells has the ability to mimic the architecture of the in vivo tumour, in particular cell–cell and cell–matrix interactions.